If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) = 3x + 23 + -1x Reorder the terms: 3(5 + 2x) = 3x + 23 + -1x (5 * 3 + 2x * 3) = 3x + 23 + -1x (15 + 6x) = 3x + 23 + -1x Reorder the terms: 15 + 6x = 23 + 3x + -1x Combine like terms: 3x + -1x = 2x 15 + 6x = 23 + 2x Solving 15 + 6x = 23 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 6x + -2x = 23 + 2x + -2x Combine like terms: 6x + -2x = 4x 15 + 4x = 23 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 4x = 23 + 0 15 + 4x = 23 Add '-15' to each side of the equation. 15 + -15 + 4x = 23 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 23 + -15 4x = 23 + -15 Combine like terms: 23 + -15 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| -y-8+6=-9+5y+1 | | 9=7(3-2x)-6(4-3x) | | X^2+-22x+120=0 | | -9+2x=15 | | 21x-9-14X+3=22X-7-15X+11 | | -15-2t=11 | | 144x^2-528x+114=0 | | 3n-2=-14 | | 142+2.7x=3571 | | 39=1.5x | | z^2+28z+192=0 | | 5x-2+78=180 | | 4-2(3-w)=18 | | (4x^2)+5x-9=0 | | 3-x=-10 | | 9x-7=9(x-7) | | 142+2.7x=7000 | | 5a=0.35 | | 4x+2=3(x-6)+6 | | (5p-5)(7p+6)= | | 8x+6-9x=2-15 | | -6m=-72 | | 3(6-b)-(-5)=-7 | | 42+(-81)+63-(58)-77= | | 7x+7-9x=15-19x+17x-8 | | 6x-7y=16 | | -15=y+15 | | 3-2[5-3(x+1)]=4x-10 | | 6p=p-40 | | (4x^2)+37x+75=0 | | z^2+13z+36=0 | | X^2-8x+84=0 |